2007
DOI: 10.1379/csc-272.1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating heat shock proteins and inflammatory markers in patients with idiopathic left ventricular dysfunction: their relationships with myocardial and microvascular impairment

Abstract: Little information is available on peripheral levels of Hsp72, Hsp60, and anti-Hsp60 antibodies in patients with left ventricular (LV) dysfunction due to non-atherosclerotic cardiac disease. In this study, serum Hsp72, Hsp60 and anti-Hsp60 antibodies, IL-6, and C-reactive protein (CRP) were measured in 44 healthy controls and in 82 patients with angiographically normal coronary arteries (LV ejection fraction [EF] > or = 50%, n=22; -35% to <50%, n=32; <35%, n=28). Patients with more severe disease (more depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…In 2000, Ridker et al [22] found elevated hs-CRP to be predictive of cardiovascular disease in women. Elevated hs-CRP has since been associated with poor prognostic indicators, such as decreased LVEF and diastolic dysfunction, in patients with a variety of cardiovascular maladies including acute myocardial infarction [23], chronic stable angina [24], left ventricular systolic heart failure [17], idiopathic left ventricular dysfunction [16], and congestive heart failure [15,25]. The results LVEF left ventricular ejection fraction, HRT/OCP hormone replacement therapy/oral contraceptive pills presented here suggest that elevated serum hs-CRP may also be useful as a biomarker for early detection of risk for cardiotoxicity in breast cancer patients undergoing adjuvant trastuzumab treatment combined with standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2000, Ridker et al [22] found elevated hs-CRP to be predictive of cardiovascular disease in women. Elevated hs-CRP has since been associated with poor prognostic indicators, such as decreased LVEF and diastolic dysfunction, in patients with a variety of cardiovascular maladies including acute myocardial infarction [23], chronic stable angina [24], left ventricular systolic heart failure [17], idiopathic left ventricular dysfunction [16], and congestive heart failure [15,25]. The results LVEF left ventricular ejection fraction, HRT/OCP hormone replacement therapy/oral contraceptive pills presented here suggest that elevated serum hs-CRP may also be useful as a biomarker for early detection of risk for cardiotoxicity in breast cancer patients undergoing adjuvant trastuzumab treatment combined with standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…BNP is synthesized in the ventricles of the heart and secreted in response to volume expansion and pressure overload; CRP is an acute phase protein produced by hepatocytes during periods of inflammation; and cTnI is located in the contractile apparatus of myocytes and is released upon necrosis. Several studies have demonstrated that BNP, hs-CRP, and/ or cTnI elevation correlates with cardiac dysfunction ranging in severity from asymptomatic decrease in LVEF to heat failure [10][11][12][13][14][15][16][17]. We hypothesized that elevated levels of serum BNP, hs-CRP, and/or cTnI may be indicative of trastuzumab-induced cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential mechanism of THinduced cardioprotection is the increased expression of heat shock proteins such as HSP-27 and HSP-70, two redox-regulated molecular chaperones that enhance cell survival under stress [123,124]. This TH effect seems particularly interesting since in patients with left ventricular dysfunction due to non-atherosclerotic cardiac disease, serum levels of heat shock proteins, IL-6 and CRP are elevated and the entity of this elevation is associated with a more severe disease as evidenced by a more depressed myocardial blood flow at rest and during dypiridamole, indicative of microvascular impairment [125].…”
Section: Effects Of Ths On Myocardial Blood Flowmentioning
confidence: 99%
“…One example is C-reactive protein (CRP), which has been shown to be highly predictive of cardiovascular disease development [20][21][22][23]. Other systemic inflammatory markers that have been associated with cardiovascular disease include interleukin-6 (IL-6) [24][25][26], white blood cell (WBC) counts [27][28][29], and fibrinogen [30,31]. Endothelial dysfunction [32,33], as well as carotid intima media thickness (IMT) [34][35][36], may also serve as surrogate endpoints of cardiovascular disease risk.…”
Section: Introductionmentioning
confidence: 99%